A tripulação de Odisseu e o proêmio da Odisseia (Nuntius Antiquus, 2014)
This work relates the presence of Odysseus’ crew and of the eating of the cattle of Helios in the first verses of the Odyssey to three narrative functions of the proem: a first definition of Odysseus and his poem; the setting of a starting point to the narrative selection; and an introduction to the Odyssean themes of human error caused by ignoring warnings and the relations between gods and humans, two themes explicitly connected in Zeus’ speech (I, 32-43). The companions are the first example of failure caused by a bad reading of the world, which leads them to the foolish decision of committing an impiety. They are also the first examples of the extreme consequences of a god’s rage.